MODELING OF THE ALUMINIUM ALLOYS CASTING PROCESSES UNDER PRESSURE - E. I. Marukovich; I. L. Zaharov; A. M. Branovitski; D. V. Dovnar (Литьë и металлургия)
The results of numerical modeling as compared to water analog are given for casing under pressure. The described approach in identification of numerical models allows to reveal their disadvantage at low costs.